Elatsoe eaudiobook - Badger, Darcie Little (Dreamscape Media, 2020)
Imagine an America very similar to our own. It's got homework, best friends, and pistachio ice cream.There are some differences. This America has been shaped dramatically by the magic, monsters, knowledge, and legends of its peoples, those Indigenous and those not. Some of these forces are charmingly every day, like the ability to make an orb of light appear or travel across the world through rings of fungi. But other forces are less charming and should never see the light of day.Elatsoe lives in this slightly stranger America. She can raise the ghosts of dead animals, a skill passed down through generations of her Lipan Apache family. Her beloved cousin has just been murdered, in a town that wants no prying eyes. But she is going to do more than pry. The picture-perfect facade of Willowbee masks gruesome secrets, and she will rely on her wits, skills, and friends to tear off the mask and protect her family.Darcie Little Badger is an extraordinary debut talent in the world of speculative fiction.